TAGLN2 is a candidate prognostic biomarker promoting tumorigenesis in human gliomas - Han, Ming-Zhi (J Exp Clin Cancer Res, 2017)
BACKGROUND: Transgelin-2 (TAGLN2) is a member of the calponin family of actin-bundling proteins that is involved in the regulation of cell morphology, motility, and cell transformation. Here, the clinical significance and potential function of TAGLN2 in malignant gliomas were investigated. METHODS: Molecular and clinical data was obtained from The Cancer Genome Atlas (TCGA) database. Gene ontology and pathway analysis was used to predict potential functions of TAGLN2. RNA knockdown was performed using siRNA or lentiviral contructs in U87MG and U251 glioma cell lines. Cells were characterized in vitro or implanted in vivo to generate orthotopic xenografts in order to assess molecular status, cell proliferation/survival, and invasion by Western blotting, flow cytometry, and 3D tumor spheroid invasion assay, respectively. RESULTS: Increased TAGLN2 expression was associated with increasing tumor grade (P < 0.001), the mesenchymal molecular glioma subtype and worse prognosis in patients (P < 0.001). Immunohistochemistry performed with anti-TAGLN2 on an independent cohort of patients (n = 46) confirmed these results. Gene silencing of TAGLN2 in U87MG and U251 significantly inhibited invasion and tumor growth in vitro and in vivo. Western blot analysis revealed that epithelial-mesenchymal transition (EMT) molecular markers, such as N-cadherin, E-cadherin, and Snail, were regulated in a manner corresponding to suppression of the EMT phenotype in knockdown experiments. Finally, TAGLN2 was induced ~ 2 to 3-fold in U87MG and U251 cells by TGFβ2, which was also elevated in GBM and highly correlated with TAGLN2 mRNA levels (P < 0.001). CONCLUSIONS: Our findings indicate that TAGLN2 exerts a role in promoting the development of human glioma. The regulation and function of TAGLN2 therefore renders it as a candidate molecular target for the treatment of GBM. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-017-0619-9) contains supplementary material, which is available to authorized users.